Pengaruh Keterampilan Mengajar Guru Dan Minat Belajar Terhadap Prestasi Belajar Siswa Di KelaS XI TBSM SMK HKBP Pematang Siantar Tahun Ajaran 2022/2023 - Afni Cory Sitanggang; Sepriandison Saragih; Restua Hutahaean (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2022)
This study aims to determine whether there is an Influence of Teacher Teaching Skills and Learning Interests on Student Learning Achievement in Civic Education Subjects in Class XI TBSM SMK HKBP Pematang Siantar Academic Year 2022/2023. The population and sample in this study were class XI as many as 53 people. To obtain data on teachers' teaching skills and interest in learning, researchers used questionnaires as a data collection tool consisting of four options assessed through availability and reliability tests. the two variables above were first tested for chi squared and it turned out that both variables were normal. then the hypothesis is tested by calculating the linear regression equation, namely Y on X1, Y on X2 linear with Y and Y on X1 and X2 linear with Y. The coefficients of influence obtained are as follows: Based on the significance test of the effect (t test) by rejecting H0 and accept H1, then it is obtained: The effect of Teacher Teaching Skills and Learning Interest together on student learning achievement.